Morphology and electrochromic property of chemical bath deposited NiO films at different NiSO4 concentration - THONGJOON, Watcharaporn; AIEMPANAKIT, Kamon; CHUASONTIA, Itsarapong; AIEMPANAKIT, Chantana (Journal of Metals, Materials and Minerals, 2022)
In this study, nickel oxide (NiO) films were prepared on indium tin oxide (ITO) glass by a chemical bath deposition (CBD) at different nickel sulfate (NiSO4) concentrations. The NiO films were verified for their structural properties with field emission scanning electron microscopy (FE-SEM) and X-ray diffraction (XRD) while the optical properties were investigated using a spectrophotometer. Moreover, the NiO films were studied to assess their electrochemical properties by cyclic voltammetry in potassium hydroxide (KOH) electrolyte. The results showed that annealed NiO films exhibited the dominant crystal structure of the (111) plane. Meanwhile, the NiSO4 concentration controlled morphological structure between dense and porous structures. The porous structure of NiO film was produced with the NiSO4 concentration in the range of 0.2 M to 1.0 M and the most porous structure was NiSO4 concentration at 0.8 M with a porosity of 64.56%. The optical contrast was calculated between bleached and colored states which were obtained at a maximum of 51.39% for NiO films at 0.8 NiSO4 concentration. Morphological effects and electrochromic properties were highly consistent. Analysis of the cyclic voltammetry (CV) results revealed that the cyclic stability for the highly porous structure of NiO films was more deteriorating than the less porous films.